Digital Marketing Strategies and Consumer Behaviour: Insights into Online Purchase Intention for Halal Cosmetics in Malaysia - Hasim, Muhammad Asyraf; Harun, Amran; Ibrahim, Fatimah Ibrahim; Hassan, Sallaudin; Ishak, Mohd Fikri (2025)
This study examines digital marketing strategies and consumer behaviour, focusing on online purchase intention for halal cosmetics in Malaysia as purchasing shifts from physical stores to online platforms post-COVID. It introduces a novel framework investigating the direct and indirect effects of social media engagement, halal brand awareness, and halal brand quality on online purchase intention, with attitude as a mediating factor, based on the Theory of Planned Behavior (TPB). An online survey was conducted in 2024 among 268 Muslim females aged 18 to 26 (Gen Z) using 5-point Likert scale questions and convenience random sampling, with data analysed through partial least squares structural equation modelling (PLS-SEM). Findings reveal that social media engagement, halal brand awareness, and halal brand quality significantly influence online purchase intention, with attitude as a crucial mediator in these relationships. These results highlight the importance of fostering positive consumer attitudes through effective social media engagement, strong halal branding, and an emphasis on product quality. Future research could expand the framework to include older demographics, additional regions, and moderating factors like income level, education, and electronic word-of-mouth (eWOM) to provide deeper insights into online purchasing behaviours for halal cosmetics.